2017
DOI: 10.1515/abm-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipids and brain-derived neurotrophic factor in a cross-section of male students with symptoms of depression at a university in Iran: an observational study

Abstract: Background Depression is a neuroprogressive disorder that is characterized by neurotransmitter derangement and decreased neurogenesis and neurotrophic factors including brain-derived neurotrophic factor (BDNF). Objectives To determine the lipid profiles and BDNF levels in university students at an institution in Iran and association of these factors with Beck Depression Inventory (BDI) scores. Methods We conducted an observational study of a cross-section of male students at the Ahvaz Jundishapur University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Male university students with the disorder showed reduced plasma BDNF levels. Their levels were measured using Beck-II, without linking to academic overload ( Tavakoli et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Male university students with the disorder showed reduced plasma BDNF levels. Their levels were measured using Beck-II, without linking to academic overload ( Tavakoli et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also find that a high intake of cholesterol can lower BDNF serum level as seen in group 2 and significantly different compared to group 1 as shown in Table 1 (p=0.003). Some researchers have reported that high serum cholesterol can lower the level of BDNF (Tavakoli et al 2018;Sustar et al 2019), as well as may ruin plasticity neurons and the integrity of BBB (Freeman and Granholm 2012). BDNF lowest concentration as seen in group 2 may be due to the damage of BBB which involved as a transport pathway blood-brain BDNF (Klein et al 2011;Naegelin et al 2018;Gejl et al 2019).…”
Section: Effect Of Co and Cost On Bdnf Serummentioning
confidence: 95%